Automated Students Attendance System - Diane Teng , Sim Lean (2009)
The Automated Students' Attendance System is a system that takes the attendance of students in a class automatically. The system aims to improve the current attendance system that is done manually. This work presents the computerized system of automated students' attendance system to implement genetic algorithms in a face recognition system. The extraction of face template particularly the T-zone (symmetrical between the eyes, nose and mouth) is performed based on face detection using specific HSV colour space ranges followed by template matching. Two types of templates are used; one on edge detection and another on the intensity plane in YIQ colour space. Face recognition with genetic algorithms will be performed to achieve an automated students' attendance system. With the existence of this attendance system, the occurrence of truancy could be reduced tremendously.